Exploring biorepository donation patterns, experiences, and recommendations: a mixed-methods study among Appalachian adults enrolled in a sugary drink reduction program - Brock, Donna-Jean P.; Markwalter, Theresa; Li, Li; Venkatesh, Samyukta; Helms, Cheyanne; Reid, Annie; Zoellner, Jamie M. (Frontiers in Public Health, 2024)
Background Under-represented subgroups in biomarker research linked to behavioral health trials may impact the promise of precision health. This mixed methods study examines biorepository donations across an Appalachian sample enrolled in a sugary drink reduction intervention trial. Methods Participants enrolled in the behavioral trial were asked to join an optional biomarker study and were tracked for enrollment and biospecimen returns (stool and/or buccal sample). At 6 months, participants completed a summative interview on decision-making process, experiences collecting samples, and recommendations to encourage biospecimen donation. Return rates were analyzed across demographics (i.e., age, gender, race, education, income, health literacy status, and rurality status) using chi-squares. Qualitative data were content coded with differences compared by biomarker study enrollment and donation choices. Results Of the 249 invited participants, 171 (61%) enrolled, and 63% (n = 157) returned buccal samples and 49% (n = 122) returned stool samples. Metro residing participants were significantly more likely (56%) to return stool samples compared to non-metro (39%) counterparts [x2(1) = 6.61; p = 0.01]. Buccal sample return had a similar trend, 67 and 57%, respectively for metro vs. non-metro [x2(1) = 2.84; p = 0.09]. An additional trend indicated that older (≥40 years) participants were more likely (55%) to donate stool samples than younger (43%) participants [x2(1) = 3.39; p = 0.07]. No other demographics were significantly associated with biospecimen return. Qualitative data indicated that societal (66–81%) and personal (41–51%) benefits were the most reported reasons for deciding to donate one or both samples, whereas mistrust (3–11%) and negative perceptions of the collection process (44–71%) were cited the most by those who declined one or both samples. Clear instructions (60%) and simple collection kits (73%) were donation facilitators while challenges included difficult stool collection kits (16%) and inconveniently located FedEx centers (16%). Recommendations to encourage future biorepository donation were to clarify benefits to science and others (58%), provide commensurate incentives (25%), explain purpose (19%) and privacy protections (20%), and assure ease in sample collection (19%). Conclusion Study findings suggest the need for biomarker research awareness campaigns. Researchers planning for future biomarker studies in medically underserved regions, like Appalachia, may be able to apply findings to optimize enrollment.